The Turn towards Regional Trade Agreements: Is EAC Welfare Enhancing to Partner States? - Seth Omondi Gor (Journal of World Trade Studies, 2011)
This study attempts to assess the welfare effects of EAC on partner states in the backdrop of multiple memberships in different Regional Trade Agreements. Using UN COMTRADE databas at 6 digit level of aggregation with HS96 nomenclature, we estimate a number of trade indicator with a view to evaluating the composition of trade structures, trade flows, the degree of opennes of the economies, and the potential for trade diversion or creation, all of which have critical implications for EAC’s integration process. On the basis of these indicators, we find that EAC is welfare enhancing to partner states.